2006
DOI: 10.1074/jbc.m604310200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Tight Junction-associated Protein, Zonula Occludens-1, in Sphingosine 1-Phosphate-mediated Endothelial Chemotaxis and Barrier Integrity

Abstract: In this report, sphingosine-1-phosphate (S1P), a serum-borne bioactive lipid, is shown to activate tight-junction-associated protein Zonula Occludens-1 (ZO-1), which in turn plays a critical role in regulating endothelial chemotaxis and barrier integrity. After S1P stimulation, ZO-1 was redistributed to the lamellipodia and cell-cell junctions via the S1P1/G i /Akt/Rac pathway. Similarly, both endothelial barrier integrity and cell motility were significantly enhanced in S1P-treated cells through the G i /Akt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 35 publications
6
169
0
Order By: Relevance
“…Subsequently, HGECs were transfected with 100 pmol of small interfering TLF4 (siTLR4; Dharmacon), siRNA to laminin (Dharmacon), 100 nM siIRF3 (Dharmacon), or 1 g of lentiviral vector carrying siRNA to S1P1 (28) using the electroporation technique (Amaxa). Briefly, when the cells reached 70% confluence, they were collected and then 1 ϫ 10 6 cells were incubated in 100 l of Human Keratinocyte Nucleofector Solution containing siRNA to IRF3, S1P1, TLR4, or laminin for 15 min at room temperature.…”
Section: Silencing Tlr4 S1p1 or Irf3mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, HGECs were transfected with 100 pmol of small interfering TLF4 (siTLR4; Dharmacon), siRNA to laminin (Dharmacon), 100 nM siIRF3 (Dharmacon), or 1 g of lentiviral vector carrying siRNA to S1P1 (28) using the electroporation technique (Amaxa). Briefly, when the cells reached 70% confluence, they were collected and then 1 ϫ 10 6 cells were incubated in 100 l of Human Keratinocyte Nucleofector Solution containing siRNA to IRF3, S1P1, TLR4, or laminin for 15 min at room temperature.…”
Section: Silencing Tlr4 S1p1 or Irf3mentioning
confidence: 99%
“…S1P1 signals through the G i/O proteins; however, S1P2 and S1P3 stimulate G q and G 12/13 (19), and S1P5 activates both G 12/13 and G i (20). S1P has been extensively studied for its healing and repair cell functions, such as cell migration (21) and tightening (22), but its role in inflammation is largely unknown particularly in epithelial cells. LPS-induced IFN-␤ expression (23) has been extensively studied in mammalian cells, including dendritic cells and macrophages (7); however, a detailed investigation of the regulation of IFN-␤ in epithelial cells is lacking.…”
mentioning
confidence: 99%
“…In fact, interactions between S1P, SK and various catenin family members have been described. [79][80][81][82][83] A recent study demonstrated that Sphk1, the major enzyme necessary for synthesizing S1P, is required for enlargement of Min mouse adenomas, since Min mice that do not express this enzyme develop only small adenomas, in contrast to the significant number of large adenomas that developed in Min mice with intact Sphk1 expression. 84 Importantly, both S1P and sphingosine levels were high in Min mouse polyps compared to normal adjacent tissues, indicating that sphingolipid metabolism is abnormal in the neoplastic tissue.…”
Section: S1p Lyase Sownregulation In Intestinal Tumorigenesismentioning
confidence: 99%
“…Sphingosine-1-phosphate regulates vascular integrity through several mechanisms, including the modulation of junctional protein expression and localization (Adamson et al, 2010;Lee et al, 2006;Wang and Dudek, 2009). Only recently has this sphingolipid pathway been considered as a potential stroke therapeutic (Czech et al, 2009;Hasegawa et al, 2010;Wacker et al, 2009;Wei et al, 2011).…”
Section: Introductionmentioning
confidence: 99%